Modulation of azimuth tuning plasticity in rat primary auditory cortex by medial prefrontal cortex. (7th April 2017) - Gao, Lixia; Li, Xinjian; Yang, Wenwei; Sun, Xinde
Highlights: Adult rats A1 exhibited azimuth tuning plasticity when acoustic stimuli were played at 5° or 10° away from best azimuth. The best azimuth shifted toward the exposure azimuth when repeated acoustic stimuli were played for 20–60 min. A shorter exposure time and longer decay time were required the less the angle deviated from the best azimuth. A1 neuron azimuth tuning plasticity was modulated by the mPFC via affecting the induction and decay time. Abstract: Neurons in the primary auditory cortex (A1) of adult animals exhibit short-term plasticity of frequency selectivity and tonotopic organization in behavioral contexts ranging from classical conditioning to attention tasks. However, it is still largely unknown whether short-term plasticity of spatial tuning takes place in A1 of adult animals and whether this spatial turning plasticity in A1 of adults is mediated by medial prefrontal cortex (mPFC) as there are reciprocal connection between mPFC and auditory cortex (AC). In the present study, we used extracellular recordings to test whether azimuth tuning in A1 of anesthetized rats can be reshaped by repeated sound stimuli at neurons' non-preferred azimuth. We also identified whether and how such A1 azimuth tuning plasticity was modulated by the neural activities of mPFC. Our results showed that A1 neurons in adult rats have azimuth tuning plasticity when repeated acoustic stimuli were delivered at the azimuth with a deviation by less than 15° from the best azimuth (BA). The BA shifted toward the exposure azimuth when repeated acoustic stimuli were played for 20–60 min and plasticity decayed within one hour. The less the angle deviated from the BA, the shorter exposure time and longer decay time were required to induce azimuth tuning plasticity. Neural activity in mPFC modulated azimuth tuning plasticity of A1 neurons as reflected by the shorter induction time when mPFC was activated by focal electrical stimulation and the longer induction time when mPFC was inactivated by drug application. Our results suggest that spatial location selectivity in A1 neurons remains plastic in mature animals and that short-term plasticity of spatial tuning can be modulated by the neural activities of mPFC.